Groundwater recharge in a steep mountain slope and its implications for slope stability: Åknes rockslide (Norway) - Sena, Clara; Papadimitrakis, Ioannis; Braathen, Alvar; Aspaas, Andreas; Pless, Gustav; Kittilä, Anniina; Ordens, Carlos Miraldo (Frontiers in Earth Science, 2025)
The Åknes rockslide lies in a steep mountain slope, dipping on average 30 to 35° towards Sunnylv Fjord, Western Norway. As part of the early-warning system implemented for this rockslide, hydraulic heads have been continuously monitored since 2007. Four multi-level boreholes established in 2017–2018 provided an unprecedent dataset to better understand groundwater recharge in such geological setting. Hydraulic-head timeseries reveal high and opposing trends of up to 3.5 and −6.3 m/year, which could be related to the continuous alteration of the geometry and permeability of the water-carrying fracture network, due to rockmass creeping and widening of tension fractures. Deeper than 80 m below ground, hydraulic heads change from underpressured conditions in Spring to overpressured conditions in Autumn. The seasonal peak in hydraulic heads, coinciding with overpressured conditions, is a major concern in an eventual acceleration of the rockslide. Water infiltration is favoured in vertical fracture zones and local topographic depressions, such as the backscarp, while the connectivity of the sub-vertical fractures allows infiltrating water to reach the water table at 33–78 m depth, contributing to groundwater recharge. Water is available for infiltration in periods with near frost- and snow-free ground (May to November), with considerably higher amounts of water from May to June due to higher snowmelt rates. These results provide a better understanding of the hydrological regime and recharge processes in a steep mountain slope and their implications for the management of unstable slopes.